Use of fosfomycin compared with ceftriaxone and meropenem for the treatment of urinary tract infections due to multidrug-resistant Escherichia coli (the FOREST study): Critically appraised article - Zela-Coila, Frank (2023)
Presentation:  In this article, we present our critical assessment of a pragmatic clinical trial published in the Jama Network Open journal in the year 2022. Study conclusions: The study fails to demonstrate the non-inferiority of 4g of intravenous disodium fosfomycin every 6 hours over 60 minutes compared to ceftriaxone (1g of intravenous ceftriaxone every 24 hours over 2-4 minutes) or, if resistant to ceftriaxone, meropenem (1g of intravenous meropenem every 8 hours over 15-30 minutes). Critical comment: The article is relevant because bacterial resistance is currently of interest for the proper management of urinary tract infections. Therefore, alternatives that are not empirically used are being sought. However, the study has limitations such as not reaching the calculated sample size, having a low margin of non-inferiority, and the lack of blinding in the intervention.